Associations between maternal urinary kisspeptin in late pregnancy and decreased fetal growth: a pregnancy-birth cohort study - Chen, Jiaxian; Yang, Lan; Chen, Yafei; Yuan, Wei; Chen, Yao; Liang, Hong; Miao, Maohua; He, Gengsheng; Wang, Ziliang (Frontiers in Endocrinology, 2024)
Background: Kisspeptin has been indicated to be a biomarker of fetal growth. Although some evidence suggested that maternal kisspeptin concentrations in early pregnancy were associated with increased fetal growth, studies are still limited and the effect of kisspeptin in late pregnancy remains unknown. This study aimed to investigate the associations between maternal kisspeptin in late pregnancy and fetal growth. Methods: Based on the Shanghai-Minhang Birth Cohort study, 724 mother-neonate pairs were included in this study. We measured maternal kisspeptin concentrations in the urine samples collected in late pregnancy and neonatal anthropometric indices at birth. The associations between maternal kisspeptin and neonatal anthropometry were investigated using multiple linear regression models. Results: Higher maternal urinary kisspeptin concentrations were associated with lower neonatal birth weight, head circumference, upper arm circumference, abdominal skinfold thickness, triceps skinfold thickness, and back skinfold thickness. The inverse associations were more pronounced for the highest kisspeptin levels versus the lowest. These patterns were consistent in analyses stratified by neonatal sex, with notably stable associations between maternal kisspeptin concentrations and skinfold thickness. Conclusions: The present study suggested that maternal kisspeptin concentrations in late pregnancy might be inversely associated with fetal growth. The physiological mechanisms of maternal kisspeptin might differ from those in early pregnancy. Further studies are required to assess associations between maternal kisspeptin and energy homeostasis and explore the physiological roles of kisspeptin in late pregnancy.